Propagation of Laguerre-Gaussian beam intensities through optically thick turbid media - Ganesh M. Balasubramaniam; Gokul Manavalan; Shlomi Arnon (Scientific Reports)
Abstract Recent research has increasingly focused on Laguerre-Gaussian (LG) beams carrying a topological charge (l) due to their demonstrated ability to enhance signal transmission through turbid media. This promising phenomenon has spurred considerable interest in understanding the complex propagation dynamics of such beams, with the goal of optimizing optical systems for highly scattering environments. In this study, we experimentally investigate the transmission characteristics of LG beams with various topological charges as they propagate through a turbid multiple-scattering medium at different depths. By analyzing the resulting transmission data, we calculate the scattering mean free path ( $$\:{{Λ\:}}^{*}$$ ) for each LG mode and show that $$\:{{Λ\:}}^{*}$$ increases with increasing values of l. Moreover, we show that beams with higher topological charges traverse greater distances within diffuse media while retaining their characteristic donut shape using Monte Carlo simulations. Our findings provide an empirical characterization of the relationship between topological charge and scattering mean free path and also explain the improved transmission with increasing l, at least until optical depths of ~ 40 $$\:{{Λ\:}}^{*}$$ , highlighting potential trends that warrant further investigation regarding the potential of applying Laguerre-Gaussian beams for enhanced optical imaging and spectroscopy through highly scattering media.